AI Desktop Partner Facial Expression Detection - Gawade, AS; Gaikwad, YC; Lambar, AT (International Journal of Computer Sciences and Engineering, 2020)
In this paper focuses on a system of recognizing human’s emotion detected from a human’s face. The analysed information is conveyed by the regions of the eye’s and the mouth and the image is compared with the database created which consist of various facial expressions pertaining to six universal basic facial emotions. The methodology uses a classification technique of information into a new fused image which is composed of two blocks integrated by the area of the eyes and mouth, very sensitive areas to changes human’s expressions. This system focuses on the facial expressions and by detecting them it helps to relieve the stress of the user by providing the various platforms such as the Chat Bot, Music Player, etc. this is based on the detected expressions of the user and the system uses the machine learning for this purpose.